2015
DOI: 10.2527/jas.2014-8699
|View full text |Cite
|
Sign up to set email alerts
|

The optimum ratio of standardized ileal digestible leucine to lysine for 8 to 12 kg female pigs1

Abstract: ABSTRACT:The objective of the study was to estimate Leu requirement for weaned piglets to balance indispensable AA in reduced CP diets. A dose-response experiment was conducted to estimate the standardized ileal digestible (SID) Leu to Lys ratio required for the maximum growth of young pigs after weaning. In this study, 96 female pigs (initial BW of 8 kg) were allotted to 1 of 6 dietary treatments with 16 individually penned pigs per treatment. Graded levels of crystalline l-leu were added to a basal diet to p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 19 publications
0
19
0
Order By: Relevance
“…The AIC, which was used to evaluate the adequacy of the models, showed that the quadratic-function model was an appropriate model for estimating the Leu requirement. The quadratic-function analysis revealed that the SID Leu : Lys level required to optimise growth was, on average, 108%, which is markedly higher than the estimates of 102% obtained by Gloaguen et al (2013a) and 93% obtained by Soumeh et al (2015) and is also higher than the estimate of 100% recommended by the NRC (2012). The observed effects of the high-Leu diets on FI and growth can probably be explained by the recently described anorexigenic effect of Leu (Cota et al, 2006;Wiltafsky et al, 2010;Wessels et al, 2016) and the finding that an excessive consumption of Leu may induce its own degradation via an irreversible oxidative-decarboxylation reaction by the BCKDH complex, which limits growth (Wiltafsky et al, 2010;Wessels et al, 2016).…”
Section: Discussionmentioning
confidence: 62%
See 1 more Smart Citation
“…The AIC, which was used to evaluate the adequacy of the models, showed that the quadratic-function model was an appropriate model for estimating the Leu requirement. The quadratic-function analysis revealed that the SID Leu : Lys level required to optimise growth was, on average, 108%, which is markedly higher than the estimates of 102% obtained by Gloaguen et al (2013a) and 93% obtained by Soumeh et al (2015) and is also higher than the estimate of 100% recommended by the NRC (2012). The observed effects of the high-Leu diets on FI and growth can probably be explained by the recently described anorexigenic effect of Leu (Cota et al, 2006;Wiltafsky et al, 2010;Wessels et al, 2016) and the finding that an excessive consumption of Leu may induce its own degradation via an irreversible oxidative-decarboxylation reaction by the BCKDH complex, which limits growth (Wiltafsky et al, 2010;Wessels et al, 2016).…”
Section: Discussionmentioning
confidence: 62%
“…In 2013, Gloaguen et al (2013a and2013b) estimated the Leu requirement of piglets based on a curvilinear-plateau model and suggested that 102% was an appropriate SID Leu : Lys level to maximise the daily gain of piglets fed a low-CP diet. However, Soumeh et al (2015) found that a SID Leu : Lys level of 93% was sufficient to maximise growth in 8 to 12 kg female piglets. Leu is an indispensable AA, but it may also have adverse effects on feed intake (FI) and growth when given in excess amounts in relation to other AA, particularly in relation to valine and isoleucine.…”
Section: Introductionmentioning
confidence: 99%
“…Metabolism of BCAAs are known to interact with each other, and it is generally believed that excessive supply of dietary leucine leads to catabolism of isoleucine and valine [7,8]. However, recently excessive supply of isoleucine was shown to reduce growth in post-weaning of pigs [7], whereas, the excessive supply of leucine or valine had no negative effects on growth performance [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…Diets from the 3 previous studies (Soumeh et al, 2014;Soumeh et al, 2015a;Soumeh et al, 2015b) were stored at -20 °C and used in the 3 new experiments. The diets were based on wheat, barley, and fermented soybean meal as the main ingredients and were formulated to provide the same nitrogen and NE content ( Table 1).…”
Section: Animals and Dietsmentioning
confidence: 99%
“…A common approach to studying AA requirement is to run dose-response experiments where body weight gain and feed intake are evaluated for 2 to 4 weeks. In our previous 3 studies on Ile (Soumeh et al, 2014), Leu (Soumeh et al, 2015a), and Val (Soumeh et al, 2015b), the requirement of those AA was estimated for 8 to 18 kg pigs by evaluating feed intake and weight gain during 2 weeks, but also by quantifying AA and other metabolites in the blood and urine. In these studies, a general trend of a decrease in plasma AA concentrations with increasing provision of the limiting AA was observed which can be indicative of improved AA utilization for growth.…”
Section: Introductionmentioning
confidence: 99%